Effect of different post-processing conditions on the accuracy of liquid crystal display-printed orthognathic surgical splints - Siripatra Patchanee; Pokpong Amornvit; Maneethip Mortin; Narissaporn Chaiprakit (Heliyon)
Objectives: To evaluate the accuracy (trueness and precision) of liquid crystal display (LCD)-printed orthognathic surgical splints under two different post-processing conditions—rinsing solvent and post-polymerization time. Materials and methods: An LCD 3D printer was used to create 48 surgical splints using the same reference standard tessellation language (STL) files. They were randomly assigned to two experimental studies. In the rinsing solvent study, 24 surgical splints were divided into three groups (n = 8) based on their rinsing solvents: isopropyl alcohol (IPA), ethanol, and water. In the post-polymerization time study, 24 surgical splints were divided into three groups (n = 8) based on the post-polymerization time: (3, 6, and 10 min). The surgical splints were covered with an opaque scanning spray, scanned, and converted into STL files. The images were trimmed and superimposed onto the reference STL file to evaluate trueness and precision, and the deviation was calculated using the root mean square (RMS) formula. Color map data were also obtained. The RMS was statistically analyzed using one-way analysis of variance and Tukey's test (α < 0.05). Results: The lowest RMS values of trueness and precision were observed in the IPA group and the 6-min post-polymerization time groups (p < 0.05). The IPA-rinse and 6-min polymerization groups (p < 0.05) demonstrated the highest accuracy for LCD-printed orthognathic surgical splint fabrication. Conclusion: The dimensional accuracy of LCD-printed surgical splints is affected by the post-processing conditions, including the rinsing solvent and polymerization time. The RMS and color map data associated with the IPA-rinse and 6-min polymerization corresponded to the highest accuracy.